Punching shear resistance of strengthened reinforced concrete interior slab–column connections using ultra-high-performance strain-hardening cementitious composite material. Issue 8 (June 2019) - Afefy, Hamdy M; El-Tony, El-Tony M
The main target of this article is to find out the most applicable strengthening technique to change the brittle punching shear failure of slab–column connection to a ductile one. The considered strengthening technique uses the combined effect of the internal single-leg stirrups and a thin layer of ultra-high-performance strain hardening cementitious composite material provided in either tension or compression side. Thus, 12 slab specimens divided into four groups were prepared and configured. It was found that the slab provided with properly anchored single-leg stirrups with a cross-shaped thin layer of ultra-high-performance strain hardening cementitious composite material at the compression side proved the most efficient technique among all the considered configurations. This technique enabled the slab to sustain a punching load of about 2.38 times that of the control unstrengthened slab. In addition, it exhibited ductile failure showing strain hardening and softening plateaus. Finally, the experimental shear resistances of all the strengthened slabs were compared against the design resistances stipulated by different design standards such as the ECP 203-2007, ACI 318-14, DIN 1045-1, and EC2-2004 codes. It can be concluded that the failure characteristics stipulated by the DIN 1045-1 code showed the most rational results compared with those of the experimental findings.